Fixed-combination, low-dose, triple-pill antihypertensive medication versus usual care in patients with mild-to-moderate hypertension in Sri Lanka: a within-trial and modelled economic evaluation of the TRIUMPH trial. Issue 10 (October 2019) - Lung, Thomas; Jan, Stephen; de Silva, H Asita; Guggilla, Rama; Maulik, Pallab K; Naik, Nitish; Patel, Anushka; de Silva, Arjuna P; Rajapakse, Senaka; Ranasinghe, Gotabhaya; Prabhakaran, Dorairaj; Rodgers, Anthony; et al.
Summary: Background: Elevated blood pressure incurs a major health and economic burden, particularly in low-income and middle-income countries. The Triple Pill versus Usual Care Management for Patients with Mild-to-Moderate Hypertension (TRIUMPH) trial showed a greater reduction in blood pressure in patients using fixed-combination, low-dose, triple-pill antihypertensive therapy (consisting of amlodipine, telmisartan, and chlorthalidone) than in those receiving usual care in Sri Lanka. We aimed to assess the cost-effectiveness of the triple-pill strategy. Methods: We did a within-trial (6-month) and modelled (10-year) economic evaluation of the TRIUMPH trial, using the health system perspective. Health-care costs, reported in 2017 US dollars, were determined from trial records and published literature. A discrete-time simulation model was developed, extrapolating trial findings of reduced systolic blood pressure to 10-year health-care costs, cardiovascular disease events, and mortality. The primary outcomes were the proportion of people reaching blood pressure targets (at 6 months from baseline) and disability-adjusted life-years (DALYs) averted (at 10 years from baseline). Incremental cost-effectiveness ratios were calculated to estimate the cost per additional participant achieving target blood pressure at 6 months and cost per DALY averted over 10 years. Findings: The triple-pill strategy, compared with usual care, cost an additional US9·63 (95% CI 5·29 to 13·97) per person in the within-trial analysis and 347·75 (285·55 to 412·54) per person in the modelled analysis. Incremental cost-effectiveness ratios were estimated at 7·93 (95% CI 6·59 to 11·84) per participant reaching blood pressure targets at 6 months and 2842·79 (−28·67 to 5714·24) per DALY averted over a 10-year period. Interpretation: Compared with usual care, the triple-pill strategy is cost-effective for patients with mild-to-moderate hypertension. Scaled up investment in the triple pill for hypertension management in Sri Lanka should be supported to address the high population burden of cardiovascular disease. Funding: Australian National Health and Medical Research Council.